Association of cholecystectomy with osteoporosis risk: a prospective study using data from the UK Biobank - Yang, Qin; Wang, Ming; Zhang, Tongtong; Wen, Jun; Long, Lu; Xia, Congying (Frontiers in Endocrinology, 2023)
Objective: To investigate whether prior cholecystectomy is associated with incident osteoporosis. Background: Cholecystectomy may cause abnormal metabolic consequences. Studies investigated the association between prior cholecystectomy and osteoporosis yield inconsistent results. Methods: In total, 17,603 UK biobank participants underwent cholecystectomy and 35,206 matched controls were included in this study. They were followed up for the incidence of osteoporosis which was determined using ICD-10 codes (M80-82). The association between cholecystectomy and osteoporosis was assessed using cox proportional regression modeling. The association between osteoporosis risk and cholecystectomy was further analyzed across age groups, sex and serum vitamin D levels and BMI categories. Results: Within a median follow-up of 13.56 years, 3217 participants were diagnosed with osteoporosis. After adjusting for relevant confounders, prior cholecystectomy was associated with 1.21-times higher risk of osteoporosis in females (HR: 1.21 [95% CI, 1.12-1.31], p<0.001) and 1.45-times higher risk in males (HR: 1.45 [95% CI, 1.10-1.90], p=0.007). In women, the association was stronger who were aged 40-55 years, with BMI <18.5 kg/m2 and vitamin D between 30 to 50 nmol/ml. No significant interaction was identified between cholecystectomy and incident osteoporosis by income levels, education levels, presence of hypertension and diabetes groups in both sexes. Conclusions: Our findings found that people underwent a cholecystectomy had a higher risk of developing osteoporosis after adjustment for potential confounders. Our findings suggest that awareness of the risk of osteoporosis is deserved in patients with a history of cholecystectomy.